Pengaruh Karakteristik Pekerjaan dan Komitmen Kerja Karyawan Terhadap Kepuasan Kerja Karyawan di PT Santos Jaya Abadi – Sidoarjo Plant - Andaresta, Aurellyta Putri (Research Journal of Social Science and Economics, 2025)
Job Characteristics refer to the variety of tasks and job characteristics given to employees who play a significant role in the success and sustainability of a company. It is one of the factors that influence employee job satisfaction. This research aims to analyze the influence of Job Characteristics and Employee Job Commitment on Employee Job Satisfaction at PT Santos Jaya Abadi Sidoarjo Plant. In this company, employee job satisfaction is an important factor in retaining quality employees and improving organizational productivity. Therefore, a good understanding of the factors that influence employee job satisfaction is crucial. This approach uses a quantitative approach with data collection techniques through questionnaires distributed to employees of PT Santos Jaya Abadi - Sidoarjo Plant. The research sample consists of permanent employees who have worked at PT Santos Jaya Abadi - Sidoarjo Plant for more than one year. The collected data were analyzed using appropriate statistical techniques. The results of this study indicate that Job Characteristics, including factors such as skill variety, task identity, task significance, autonomy, and feedback, have a positive and significant relationship with Employee Job Satisfaction. This indicates that the more diverse the tasks assigned to employees, the higher the level of autonomy given, and the more feedback received, employees tend to be more satisfied with their work. Furthermore, this study also found that Employee Job Commitment has a positive and significant relationship with Employee Job Satisfaction. Employees who have a high level of commitment to the company and their jobs tend to have high satisfaction. Based on these findings, PT Santos Jaya Abadi - Sidoarjo Plant can pay attention to the importance of adequate job characteristics and building Employee Job Commitment to improve job satisfaction. In the long run, improving Employee Job Satisfaction is expected to have a positive impact on overall company productivity and performance.